Demystifying the O-GlcNAc Code: A Systems View. - Ma, J.; Hou, C.; Wu, C. (Chemical Reviews, 2022)
Post-translational modification with O-linked ?-N-acetylglucosamine (O-GlcNAc), a process referred to as O-GlcNAcylation, occurs on a vast variety of proteins. Mounting evidence in the past several decades has clearly demonstrated that O-GlcNAcylation is a unique and ubiquitous modification. Reminiscent of a code, protein O-GlcNAcylation functions as a crucial regulator of nearly all cellular processes studied. The primary aim of this review is to summarize the developments in our understanding of myriad protein substrates modified by O-GlcNAcylation from a systems perspective. Specifically, we provide a comprehensive survey of O-GlcNAcylation in multiple species studied, including eukaryotes (e.g., protists, fungi, plants, Caenorhabditis elegans, Drosophila melanogaster, murine, and human), prokaryotes, and some viruses. We evaluate features (e.g., structural properties and sequence motifs) of O-GlcNAc modification on proteins across species. Given that O-GlcNAcylation functions in a species-, tissue-/cell-, protein-, and site-specific manner, we discuss the functional roles of O-GlcNAcylation on human proteins. We focus particularly on several classes of relatively well-characterized human proteins (including transcription factors, protein kinases, protein phosphatases, and E3 ubiquitin-ligases), with representative O-GlcNAc site-specific functions presented. We hope the systems view of the great endeavor in the past 35 years will help demystify the O-GlcNAc code and lead to more fascinating studies in the years to come.